2012
DOI: 10.1186/1471-2458-12-468
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of latent tuberculosis treatment initiation and completion at a U.S. public health clinic: a prospective cohort study

Abstract: BackgroundTreatment of latent tuberculosis infection (LTBI) is a key component in U.S. tuberculosis control, assisted by recent improvements in LTBI diagnostics and therapeutic regimens. Effectiveness of LTBI therapy, however, is limited by patients’ willingness to both initiate and complete treatment. We aimed to evaluate the demographic, medical, behavioral, attitude-based, and geographic factors associated with LTBI treatment initiation and completion of persons presenting with LTBI to a public health tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 18 publications
1
51
2
Order By: Relevance
“…3 Completion rates of <50% have been reported for both children and adults when TB medications are administered by families. 4,5 There are few patient-specific factors associated with completion of therapy. Our previous studies found that region of origin, language, and the method to test for TB infection (TST versus IGRA) were not associated with completion of therapy.…”
mentioning
confidence: 99%
“…3 Completion rates of <50% have been reported for both children and adults when TB medications are administered by families. 4,5 There are few patient-specific factors associated with completion of therapy. Our previous studies found that region of origin, language, and the method to test for TB infection (TST versus IGRA) were not associated with completion of therapy.…”
mentioning
confidence: 99%
“…The acceptance and discontinuation rates of LTBI treatment vary. Only 26% of people identified with LTBI initiated their treatments in a study conducted at public health clinics in the United States; however, only 53% of them completed the treatment course [ 24 ]. Horsburgh [ 8 ] observed completion rates of 69% and 45% for 4RIF and 9INH among high-risk populations at public clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study showed that only 53% of patients completed the therapy [26]. Erkens et al [27] showed that of 1,049 children with LTBI started on LTBI treatment in 2005-2012, and 90% completed the treatment.…”
Section: Discussionmentioning
confidence: 99%